Peculiarities of Current Transport in Titanium Oxide-Silicon Heterostructures - Milovanov, Yu.S.; Gavrilchenko, I.V.; Gayvoronsky, V.Ya.; Kuznetsov, G.V.; Skryshevsky, V.A. (Ukrainian Journal of Physics, 2012)
The mechanisms of charge carrier injection into Tі–TіО2–(n, p)Sі heterostructures have been studied. The influence of the porous TiO2 structure and the silicon substrate type on the electrical characteristics of heterostructures is analyzed. The charge transfer is shown to be accompanied by the appearance of a compensating polarization charge on the surface of TiO2 nanoparticles. Correlations between the type of adsorbed molecules and the conditions of the current flow have been determined. In Ті–ТіО2–p-Sі heterostructures, a change of the ratio between the numbers of injected electrons and holes can lead to the negative-conductivity effect.